2012
DOI: 10.5812/jnp.5
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric: Reemerging of a Neglected Asian Traditional Remedy

Abstract: considering the inhibitory effect of turmeric/curcumin on cytokines and TGF-β, it seems wise to assume that supplementary turmeric/curcumin might be a candidate remedy for chronic kidney disease and possibly prevention of subsequent end stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
39
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 35 publications
1
39
0
4
Order By: Relevance
“…Vegetables, fruits and their juices contain phenolic compounds, which have antioxidant properties and are protective against atherosclerosis. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…Vegetables, fruits and their juices contain phenolic compounds, which have antioxidant properties and are protective against atherosclerosis. [3132]…”
Section: Discussionmentioning
confidence: 99%
“…The mortality rate of patients with ARF is remained 25-70%, despite the use of various pharmacologic agents (2)(3)(4)(5). Indeed, ARF frequently occurs in critically ill patients and is an independent risk factor for poor outcome.…”
Section: Introductionmentioning
confidence: 99%
“…We concluded that Teucrium polium may be associated with kidney tubular injury and that this herbal medicine should be used with caution [2]. It is well known that herbal remedies have an important role in the recovery of some disease [6–9]; however, some medicinal plants can cause renal injury. Teucrium polium has been widely used to control blood sugar in diabetes [7].…”
mentioning
confidence: 99%